Ordovician metamorphic event in the carbonate platform of the Argentine Precordillera: Implications for the geotectonic evolution of the proto-Andean margin of Gondwana - Voldman, Gustavo Gabriel (2009)
An Ordovician metamorphic event is recorded by means of conodont paleothermometry in the slope sedimentary sequences of the Western Precordillera. Allochthonous conodonts from reworked deposits of the eastern carbonate platform with CAI 4.5-5 and autochthonous conodonts from the olistostrome matrix with CAI 3 allow for constraining the metamorphic age within the Paltodus deltifer and Lenodus variabilis zones (i.e., ca. 480-465 Ma). The conodont data support an Ordovician instead of an alternative Devonian collision for the Cuyania terrane with the proto-Andean margin of Gondwana, which is consistent with the earlier proposed, but still contentious, microcontinent model. In the latter scenario, the collision of the Cuyania terrane caused unroofing and cannibalism of the leading edge of the carbonate succession and basement rocks. The erosion of these rocks supplied detritus and metamorphosed conodonts to the deeper basinal settings of the Western Precordillera. As the deformation front migrated into the peripheral foreland of the Eastern and Central Precordillera, nonmetamorphosed conodonts were eventually incorporated into the west-prograding synorogenic clastic wedge. The occurrence of allochthonous and autochthonous conodonts in the slope facies of the Western Precordillera provides a time constraint for the early accretion of the Cuyania terrane and its transition to an evolving foreland mountain system in the Ordovician period.